2021
DOI: 10.1002/asia.202100394
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Dinitrogen Activation via Transition‐Metal‐Involved [4+2] Cycloaddition Reaction

Abstract: As the strongest triple bond in nature, the N≡N triple bond activation has always been a challenging project in chemistry. On the other hand, since the award of the Nobel Prize in Chemistry in 1950, the Diels‐Alder reaction has served as a powerful and widely applied tool in the synthesis of natural products and new materials. However, the application of the Diels‐Alder reaction to dinitrogen activation remains less developed. Here we first demonstrate that a transition‐metal‐involved [4+2] Diels‐Alder cycload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 113 publications
1
10
1
Order By: Relevance
“…This value is close to the isotopomer shift calculated from reduced mass considerations (923 cm –1 ). These values are higher than those reported for the U­(VI) terminal nitride complex [NU­(Tren TIPS )] (914 and 883 cm –1 for 14 N and 15 N, respectively) but lower than the value reported for the UN 2 formed in the gas phase (1051.0 cm –1 ) …”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…This value is close to the isotopomer shift calculated from reduced mass considerations (923 cm –1 ). These values are higher than those reported for the U­(VI) terminal nitride complex [NU­(Tren TIPS )] (914 and 883 cm –1 for 14 N and 15 N, respectively) but lower than the value reported for the UN 2 formed in the gas phase (1051.0 cm –1 ) …”
Section: Resultscontrasting
confidence: 69%
“…Moreover, the secondary interactions of metal dinitrogen complexes with alkali ions are known to enhance the activity of the iron-based Haber–Bosch catalysts . Molecular complexes capable of effecting the cleavage of dinitrogen to nitrides ,, are essentially limited to d-block metals , and are all proposed to involve multimetallic intermediates , that have been isolated in a few instances. ,,, In particular, based on the structure of the final nitride complex, multimetallic cooperation of transition metals and Lewis acids, potassium in particular, has been suggested by several groups to be a crucial step in the six-electron dinitrogen cleavage to nitride involving alkali ions as reducing agents. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Holland and coworkers 12 developed a nitrogenase-inspired complex with a sulfur-rich coordination sphere, which could break the Fe-S bond and bind N 2 after reduction. In addition, some other transition metal catalysts, including cobalt, 13 chromium, 14 scandium, 15 and rhenium complexes, 16 and non-meta systems [17][18][19][20][21] have also been developed for catalytic NN bond activation. Braunschweig et al 22,23 reported binding and reduction of one or two N 2 molecules by a nonmetal dicoordinated borylene.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantage of the diversity of oxidation-state and orbital, transition metals have been used for N 2 activation and conversion into ammonia and other useful nitrogen compounds. [2][3][4][5][6][7][8][9][10][11][12][13][14] Note that the industrial Haber-Bosch process [15] for ammonia production requires relatively harsh conditions (350°to 500 °C and 150 to 200 atm), leading to consumption of more than 1% of the world's annual energy supply. Thus, developing main group systems as an alternative strategy for N 2 activation has attracted extensive attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The significant bond strength (bond dissociation energy: 945 kJ/mol) and HOMO‐LUMO gap (10.8 eV; HOMO: the highest occupied molecular orbital; LUMO: the lowest unoccupied molecular orbital) in dinitrogen (N 2 ) [1] make its activation particularly challenging. Due to the advantage of the diversity of oxidation‐state and orbital, transition metals have been used for N 2 activation and conversion into ammonia and other useful nitrogen compounds [2–14] . Note that the industrial Haber‐Bosch process [15] for ammonia production requires relatively harsh conditions (350° to 500 °C and 150 to 200 atm), leading to consumption of more than 1% of the world‘s annual energy supply.…”
Section: Introductionmentioning
confidence: 99%